Lessons learned: resolving the enigma of genetic factors in IBS - Gazouli, Maria; Wouters, Mira M.; Kapur-Pojskić, Lejla; Bengtson, May-Bente; Friedman, Eitan; Nikčević, Gordana; Demetriou, Christiana A.; Mulak, Agata; Santos, Javier; Niesler, Beate (Nature reviews. Gastroenterology & hepatology, 2016)
The pathophysiology of IBS is multifactorial with a substantial genetic component. Although a variety of genetic and epigenetic changes have been associated with different IBS subtypes, reproducible validation of these results is still outstanding and pharmacogenetic strategies have yet to be devised. Here, the COST Action BM1106 GENIEUR (epi)genetic working group gives insights into the situation to date, advances and challenges that still need addressing.
Gesehen am 15.05.2020